Artificial Intelligence and Software Testing Building systems you can trust - Smith, Adam Leon; Black, Rex, 1964-; Davenport, James; Olszewska, Joanna Dr; Rossler, Jeremias Dr; Wright, Jonathon (BCS, The Chartered Institute for IT, 2022)
AI presents a new paradigm in software development, representing the biggest change to how we think about quality and testing in decades. Many of the well known issues around AI, such as bias, manifest themselves as quality management problems. This book, aimed at testing and quality management practitioners who want to understand more, covers trustworthiness of AI and the complexities of testing machine learning systems, before pivoting to how AI can be used itself in software test automation.